The Effect Of Time Fermentation On The Physical Quality Of Cow’s Rumen Content Silage - Ton, Jusril Wina; Wie Lawa, Emma Dyelim; Hilakore, Maritje Aleonor; Lazarus, Edwin J.L (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
The study aimed to determine the effect of fermentation time on the physical quality of cow’s rumen content silage. The study used an experimental method based on a completely randomized design (CRD) with 4 treatments of incubation time and 4 replications. The composition of the silage ingredients was as follows: cow’s rumen contents 60% + rice bran 35% + palm sugar 5% + local microorganisms 40 ml. Treatment of the fermentation time was P1: four weeks, P2: six weeks, P3: eight weeks, and P4: ten weeks. The variables observed were color, texture, odor, fungus, and cow’s rumen content silage pH. The results of the Kruskall Wallis Test analysis showed that the treatment had a very significant effect (P <0.01) on texture and odor. Still, they had no significant effect (P>0.05) on color and fungus. The results of ANOVA showed that the treatment had a very significant effect (P<0.01) on the pH value. Based on the results it can be concluded that the different fermentation times affected the texture, odor, and pH value, but not affect the color and fungus existence. The best fermentation time for this research is 8 weeks.